The Relationship of Agility, Reaction Speed, and Eye-Hand Coordination to Volleyball Forearm Passing Ability - Nova Reza Ningtyas; Aziz Amrulloh (Universitas Negeri Semarang, 2025)
Volleyball, a dynamic team sport, relies heavily on mastering fundamental techniques such as forearm passing to ensure seamless gameplay and effective team strategies. The proficiency in forearm passing is influenced not only by technical skills but also by physical components, including agility, reaction time, and eye-hand coordination. This study aims to analyze the relationship between these three physical factors and forearm passing ability among volleyball players. Conducted at the Tunas Brilliant Volleyball Club, vocational high school Ma’arif NU 01 Limpung, Batang, Central Java, in December 2024, the research employed a quantitative correlational approach. A purposive sampling technique was used to select 30 active players aged 15–18 years. Data were collected through standardized tests: the Illinois Agility Run Test for agility, the Whole Body Reaction Test for reaction time, the ball throw-catch test for eye-hand coordination, and the volleyball forearm passing test for passing ability. Pearson correlation analysis revealed significant relationships: agility showed a strong negative correlation (r = -0,553, p = 0,002), reaction time a moderate negative correlation (r = -0,378, p = 0,039), and eye-hand coordination a strong positive correlation (r = 0,564, p = 0,001) with passing ability. These findings underscore the critical role of integrated physical training in enhancing passing skills. Coaches are recommended to design holistic training programs incorporating agility drills, reaction exercises, and coordination activities to optimize player performance and support long-term volleyball development.